ANALISIS KOMPETENSI PEDAGOGIK GURU GEOGRAFI DALAM PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 SMAN 5 PONTIANAK - Linda Mailiana; Sulistyarini Sulistyarini; Nur Meily Adlika (Universitas Tanjungpura, 2021)
AbstractThis reseacrh aims to determine the pedagogic competence of geography teachers in This online learning is carried out during the Covid-19 Pandemic at SMA country 5 Pontianak. This research is a qualitative descriptive research with descriptive form. Sources of data in this study are the principal, two geography teachers, and two social studies students at SMA Negeri 5 Pontianak. The data collection technique is the technique of observation, interviews and documentation. The results of the study show the following findings: (1) Mastering the characteristics of students, teachers have difficulty because the learning process is carried out online. (2) Designing Learning, teachers design learning in accordance with the circular issued by Permendikbud No. 14 of 2019 concerning the simplification of the RPP. (3) Carrying out learning, the teacher carries out learning that is carried out online by adjusting the device that has been made by the teacher. (4) Evaluation of learning outcomes, the teacher evaluates learning by repeating the subject matter given at that time and asking students which material students do not understand. (5) Developing students to actualize their various potentials, the teacher provides material by giving praise that can motivate students to get reciprocity for the learning provided. (6) Obstacles faced by teachers and students who have problems with internet quotas, less stable networks, some do not have mobile phones, those are some of the obstacles in the learning process.Keywords: Pedagogic Competence, Learning Process, Covid-19, and Obstacles